1994
DOI: 10.1152/ajplung.1994.266.5.l502
|View full text |Cite
|
Sign up to set email alerts
|

CFTR in Calu-3 human airway cells: channel properties and role in cAMP-activated Cl- conductance

Abstract: Calu-3, a cell line derived from a lung adenocarcinoma, forms tight junctions, expresses cystic fibrosis transmembrane conductance regulator (CFTR), and secretes Cl- in response to adenosine 3',5'-cyclic monophosphate (cAMP)-elevating agents. Anion conductance of Calu-3 cells was assessed with isotopic flux and patch-clamp methods at 22 degrees C. Iodide efflux was increased by cAMP-elevating agents and brief trypsin treatment. A 7.1 +/- 0.4-pS voltage-independent Cl- channel with linear current-voltage relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 0 publications
10
112
2
1
Order By: Relevance
“…In cell-attached patches we observe the same range of long and short burst durations as in excised patches, and others have observed similarly long open bursts in cell-attached patches (18,39). Moreover, we observed a decrease in long open bursts in cell-attached patches when cells were treated with ␤-ME, raising the possibility that channels in the plasma membrane may not be in a uniformly reduced state.…”
Section: Discussionsupporting
confidence: 83%
“…In cell-attached patches we observe the same range of long and short burst durations as in excised patches, and others have observed similarly long open bursts in cell-attached patches (18,39). Moreover, we observed a decrease in long open bursts in cell-attached patches when cells were treated with ␤-ME, raising the possibility that channels in the plasma membrane may not be in a uniformly reduced state.…”
Section: Discussionsupporting
confidence: 83%
“…The regulatory role of vitamin C on Cl ion channel activity was studied in Calu-3 airway cells, which express large amounts of native CFTR as their major Cl conductance (32). Using the outside-out patch clamp mode, we found that L-ascorbic acid induced openings of CFTR Cl channels when applied to the extracellular surface of the patched membrane.…”
Section: Resultsmentioning
confidence: 99%
“…2). These cells are a model for proximal airway submucosal glands, where CFTR is expressed at relatively high levels (20). The physiological significance of the CFTR-E3KARP interaction is supported by several findings.…”
Section: Co-expression Of E3karp and Ezrin With Cftr Potentiates Cftr CLmentioning
confidence: 85%